O marketing de rede como estratégia para o desenvolvimento sustentável - Kaminski, Mauricio Tessele (2011)
The third sector in Brazil is an industry with great growth potential, but due tomismanagement performed, the non-governmental organizations end up using the funds raised only for their survival. Thus, the investment made to develop the industry it is used for maintenance of Non-Governmental Organizations. Even with the support of the first sector, the state and the second sector, private companies, organizations belonging to the third sector is not structured and automatically lose credibility with the community and society, as are the image of amateur organizations, thus losing a potential allied toinvest in the sector, the individual in society. The Network Marketing is a marketing strategy from selling direct, differing only in the form of compensation of its independent distributors. This strategy when applied ethically and efficiently, resulting in a boomingmarket companies, as well as a large growth in financial matters of the organization.Through theory, more specifically in the chain of social value, we found that this marketing strategy applied in the nonprofit sector may be a way of promoting sustainable development. So the research question we sought to apply the marketingnetwork in Action Network of Social Organizations of Santa Maria / RS, through acompany to be registered, the Network Marketing Action (MRA). During the creation and implementation of the project was carried out market research, included in the marketing plan prepared, which identified ways to sensitize the local community in relation to the third sector, thus creating action strategies for project